Impact of innovation organization network on the synergy of cross-organizational technological innovation: evidence from megaproject practices in China - Zhao, Na; Fan, Dongjiao; Chen, Yun; Wu, Chunlin (Journal of Civil Engineering and Management, 2023)
The construction industry has made an indispensable contribution to China’s environmental and economic development. With the advent of the volatile, uncertain, complex, and ambiguous (VUCA) era, cross-organizational collaboration has enabled megaproject participants to engage significantly in problem-solving and technological innovation. The impact of innovation organization network on the synergy of cross-organizational technological innovation (COTI synergy) in megaprojects is imperative for theoretical researchers and engineering practitioners. Therefore, this study aims to develop a hypothetical model of innovation organization network and COTI synergy, focusing on the mediating role of interorganizational relationships and the moderating effect of the technological innovation environment. The results of 211 questionnaires from the Chinese construction industry show that innovation organization network improves COTI synergy. Trust and communication play a vital mediating role between innovation organization network and COTI synergy. Moreover, innovative culture has a significant positive moderating effect on innovation organization network and interorganizational relationships. From the perspective of organization network, this study provides new insights into the development of technological innovation management research on megaprojects, theoretical references, and practical suggestions for project teams in developing countries to improve collaborative technological innovation efficiency.